ANDALIMAN SEBAGAI BAHAN TAMBAHAN PADA SAUCE APPETIZER DI HOTEL JW MARRIOTT MEDAN - Binur Pretty Napitupulu; Abdillah Attoriq (Akademi Pariwisata Darma Agung, 2021)
Appetizer is an appetizer before the main course which is served in small portions, one or two bites (bite size) so that it can arouse and increase appetite. Additional ingredients in this case are ingredients that are added to add flavor to the sauce and can be made in such a way as to support the appearance of a dish, as well as arouse one's appetite. Andaliman is a type of vine that is still related to pepper plants with the scientific name Zanthoxylum acanthopodium. In traditional cuisine, andaliman fruit is used as a cooking spice, besides the skin, roots and leaves are also used medicinally. Andaliman contains active trigeminal compounds that function as anti-oxidants and antimicrobials that make this plant a medicine. Based on the results of research through initial observations, the authors found an appetizer dish at the JW Marriot Hotel Medan. In particular, the dressing on the dish only uses a type of sauce that has never been developed with a new type of sauce variation. The author wishes to use andaliman as an additional ingredient for sauce variations as an appetizer dish, the author is interested in using andaliman as an additional ingredient in processed sauce for appetizer dishes at the JW Marriott hotel.